2014
DOI: 10.1007/978-3-662-44371-2_25
|View full text |Cite
|
Sign up to set email alerts
|

RSA Key Extraction via Low-Bandwidth Acoustic Cryptanalysis

Abstract: Many computers emit a high-pitched noise during operation, due to vibration in some of their electronic components. These acoustic emanations are more than a nuisance: they can convey information about the software running on the computer, and in particular leak sensitive information about security-related computations. In a preliminary presentation (Eurocrypt'04 rump session), we have shown that different RSA keys induce different sound patterns, but it was not clear how to extract individual key bits. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(179 citation statements)
references
References 18 publications
0
158
0
7
Order By: Relevance
“…Accordingly, a great deal of research is conducted to find out which side channels can be used [77,138] and how they can be optimally exploited [91]. Different algorithms are analyzed with respect to their susceptibility towards these attacks [33,99,141].…”
Section: Thesis Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a great deal of research is conducted to find out which side channels can be used [77,138] and how they can be optimally exploited [91]. Different algorithms are analyzed with respect to their susceptibility towards these attacks [33,99,141].…”
Section: Thesis Statementmentioning
confidence: 99%
“…In 2013, the acoustic side channel was presented [77]. The authors show how a 4096-bit RSA key can be extracted by analyzing the acoustic frequency spectrum during decryption.…”
Section: Other Side Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying them in practice is a matter of adapting them to the corresponding hardware implementation. The security of microcontrollers has been extensively examined, and a number of fault and side-channel attacks have been found, e.g., [4,12,20,21]. Therefore, we focus on smart-card based wallets, which provide guarantees against physical and interdiction attacks and have traditionally been used for key management and cryptographic operations.…”
Section: Introductionmentioning
confidence: 99%
“…Passive side-channel attacks, or leakage attacks, such as timing attacks, power analysis attacks, acoustic attacks, and more [1,6,24,30,36,37], have proven highly detrimental. Indeed, it has been shown that leakage attacks can be used to recover the entire secret key in common implementations of the RSA [25], AES [45] and DES [35] cryptosystems. These attacks are not just theoretical, and can be launched in complex, reallife settings, e.g.…”
Section: Introductionmentioning
confidence: 99%